Demystifying the Use of Lithium Disilicate and Cubic Phase Stabilized Zirconia in Monolithic Restorations: A Literature Review - Allan Oliveira da Silva; Ilana Santos Ramalho (Portal de Periódicos da Marinha do Brasil, 2023)
The development and popularization of surgical techniques associated with dental materials led to the transformation of oral health conditions into aesthetic rehabilitation. The aim of this study was to review the literature on the use of lithium disilicate and cubic phase stabilized zirconia in monolithic restorations. The databases used were Lilacs, Pubmed/Medline, Scielo and ScienceDirect, crossing the following descriptors in English: "Zirconium", "Yttrium", "CAD-CAM", "Ceramics", "Dental Porcelain" and "Material Resistance". Monolithic indirect restorative techniques with dental ceramics coupled with the use of CAD/CAM technology have several short-and long-term advantages. Lithium disilicate and high translucency zirconia stabilized in the cubic phase are current materials and constantly evolving in dental research due to their mechanical behavior, biological, optical and aesthetic aspects, ensuring their use as materials of excellence in aesthetic and functional rehabilitation.